Effect of Capital Structure on Profitability in PT Astra International Tbk Period 2016-2020 - Arhamy Nurul Isra; M. Risal; Muh. Yusuf Q (Jurnal Mantik, 2022)
The car business is one of the pillar areas that has a great commitment to the community's economy. Not only that, this is also supported by the popular expansion for multi-purpose vehicles which is the biggest commitment to expanding the deal in Indonesia. The data used is secondary data. Secondary data is mostly as evidence, notes, or authentic reports that have been collected in files (documentation data), both distributed and unpublished. Where information is obtained from the financial statements of the organization PT Astra International Tbk for the period 2016-2020. Based on the results of multiple linear regression, namely Y=0.055-0.594X1+0.37X2 the regression equation shows that there is a negative influence between capital structure and a positive influence on profitability at PT Astra International Tbk period 2016-2020. DAR has a negative and insignificant effect on profitability. DER has a positive and insignificant effect on profitability. PT Astra International, Tbk must expand the organization to get and follow the organization's long-term utilization and temporary commitment to create organizational benefits or benefits and can attract financial backers to buy the organization's offerings or reinvestment. because for the funder, the use of the obligation can show the organization's exhibition in supervising the organization's funds. PT Astra International, Tbk must increase the profit of the organization because profit is one of the financial supporting elements that are interested in buying shares and reinvesting and the organization must hedge by making an agreement with the bank to build the cost of the organization's portion.